Lg Coda Variations in North-Central Iran - Mojtaba Naghavi; Zaher Hossein Shomali; Mehdi Zare (International Journal of Geophysics)
Ground motion records in north-central Iran have been used in order to obtain the Lg coda 𝑄, using stack spectral ratio method. The lateral variations in 𝑄0 and its frequency dependence are estimated in the 0.3–7.0 Hz frequency range which led to 𝑄=267(±32)×𝑓0.71(±0.14). The observed variations in quality factor show low values of 𝑄0 in western part of the study region where bounded by relatively high values in southern and northern parts. Since the seismicity of the study area is quite shallow the obtained results can be attributed to the upper 30 km of the crust. The Damavand volcano and its surrounding region also exhibit variations in the value of 𝑄0 which result in low and intermediate values of 𝑄0 in western and eastern parts, respectively. Current seismicity in Damavand is mostly confined to its southwestern part, whereas our results proved to possess low values of 𝑄0. In general, most of 𝑄 factor variations can be attributed to the lateral heterogeneity as well as the severity of the crustal velocity gradient, and as expected the north-central Iran is well inferred as a tectonically active region.